(untitled) - Anderson, George Wishart; (1913-2002) (U.S.A, 1979)
This book is a collection of essays by members of the Society for Old Testament Study, surveying the work done in the Old Testament field since the publication in 1951 of The Old Testament and Modern Study (ed. H. H. Rowley). The volume is not only a record of the progress of research in these areas but also a reflection of changing perspectives in Old Testament Study and an appraisal of important changes in method and approach. All the essays are well documented and provided with short bibliographies.
Keywords: Bible -- Old Testament -- Criticism, interpretation, etc